Case Report: High-dose steroid and IVIG successful treatment in a case of COVID-19-associated autoimmune encephalitis: a literature review - Liu, Chi-Hung; Chiu, Li-Chung; Lee, Chih-Chun; Chan, Tien-Ming (Frontiers in Immunology, 2023)
Autoimmune encephalitis is a rare but critical complication of COVID-19. The management of COVID-19-associated autoimmune encephalitis includes the use of steroids, intravenous immunoglobulin (IVIG), plasmapheresis, and monoclonal antibody therapy. This study presented a patient with critical COVID-19 autoimmune encephalitis who rapidly recovered after the initiation of corticosteroids and IVIG therapy. This study reviewed the current literature on the pathophysiological mechanisms, diagnosis, and management of COVID-19-associated autoimmune encephalitis.